Os estudos culturais e a crítica literária no Brasil - Geraldo Ramos Pontes Jr (Estudos de Literatura Brasileira Contemporânea)
Two decades passed after the first intense discussions on the meaning of cultural studies for the comparativism as a literary field in Brasil, this article proposes an examination that leads to positive results on the reflexions about the necessity of new positions towards the critic subject, changes on the interdisciplinary fields of comparative literature and lit erary theory, as well as the incorporated perspectives by Brazilian specialists that criticized the initial refusal to those studies.